MRI suggests increased tonicity of the levator ani in women with interstitial cystitis/bladder pain syndrome. Issue 1 (January 2016) - Ackerman, A.; Lee, Una; Jellison, Forrest; Tan, Nelly; Patel, Maitraya; Raman, Steven; Rodriguez, Larissa
Abstract Introduction and hypothesis In interstitial cystitis/bladder pain syndrome (IC/BPS), pelvic floor dysfunction may contribute significantly to pelvic pain. To determine if pelvic floor hypertonicity manifests alterations on magnetic resonance imaging (MRI) in patients with IC/BPS, we retrospectively compared pelvic measurements between patients and controls. Methods Fifteen women with IC/BPS and 15 age-matched controls underwent pelvic MRI. Two blinded radiologists measured the pelvic musculature, including the H- and M lines, vaginal length, urethral length and cross-sectional area, levator width and length, and posterior puborectalis angle. MRI measures and clinical factors, such as age, parity, and duration of symptoms, were compared using a paired, two-tailedt test. Results There were no significant differences in age, parity, or symptom duration between groups. Patients with IC/BPS exhibited shorter levator muscles (right: 5.0 ± 0.7 vs. 5.6 ± 0.8, left: 5.0 ± 0.8 vs. 5.7 ± 0.8 cm, P < 0.002) and a wider posterior puborectalis angle (35.0 ± 8.6 vs. 26.7 ± 7.9°, P < 0.01) compared with controls. The H line was shorter in patients with IC/BPS (7.8 ± 0.8 vs. 8.6 ± 0.9 cm, P < 0.02), while M line did not differ. Total urethral length was similar, but vaginal cuff and bladder neck distances to the H line were longer in patients with IC/BPS (5.7 ± 0.6 vs. 5.1 ± 0.9 cm, P < 0.02; 1.9 ± 0.4 vs. 1.4 ± 0.2 cm, P < 0.001, respectively). Conclusions Patients with IC/BPS have pelvic floor hypertonicity on MRI, which manifests as shortened levator, increased posterior puborectalis angles, and decreased puborectal distances. We identified evidence of pelvic floor hypertonicity in patients with IC/BPS, which may contribute to or amplify pelvic pain. Future studies are necessary to determine the MRI utility in understanding pelvic floor hypertonicity in patients with IC/BPS.